TGF-BETA IN THE NATURAL HISTORY OF PROSTATE CANCER - Ahel, Jamal (Acta Clin Croat, 2019)
All transforming growth factors beta (TGFß) are cytokines that regulate several cellular functions such as cell growth, differentiation and motility. They may also have a role in immunosuppression. Their role is important for normal prostate development. TGFß is active in the regulation of balance between epithelial cell proliferation and apoptosis through stromal epithelia via the androgen receptor action. TGFß protects and maintains prostate stem cells, an important population necessary for prostate tissue regeneration. However, TGFß is shown to have a contrasting role in prostate tumor genesis. In the early stages of tumor development, TGFß acts as a tumor suppressor, whereas in the later stages, TGFß becomes a tumor promoter by inducing proliferation, invasion and metastasis. In this review, we outline complex interactions that TGFß-mediated signaling has on prostate tumor genesis, focusing on the role of these interactions during the course of prostate cancer and, in particular, during disease progression.